An open-source lickometer and microstructure analysis program. (October 2018) - Raymond, Martin A.; Mast, Thomas G.; Breza, Joseph M.
Graphical abstract: Abstract: Described herein is a design for a user-constructed electronic lickometer, intended to allow users to conduct relatively simple behavioral experiments with rodents while avoiding several common stumbling blocks. Primarily, this system does not require the purchase of specialized scientific equipment or software. Additionally, it is possible for users to construct and operate this lickometer without the prerequisite of advanced knowledge of electronics or programming. Overall, the goal of this apparatus is to provide a simple and affordable alternative for users seeking to study ingestion behaviors in rodents, while still allowing the user to obtain high-resolution data and conduct sophisticated microstructural analysis of the behavior in question. All of this is achieved using low-cost and commonly available materials for the construction of the apparatus itself, and open-source software to collect and analyze data. The only substantial prerequisites for this design are a PC with a 3.5 mm microphone input and a comfortable understanding of power tools. Finally, a validation of the operation of the describe apparatus is included.